Antimicrobial Resistance Patterns: Review of the Antibiogram of a Surgical Unit in a Public Tertiary Care Hospital of Pakistan - Kathia, Usama Muhammad (Cureus, 2020)
Introduction Antimicrobial resistance (AMR) has become a challenge in modern-day medical practice. The pace at which microbes are becoming resistant to antibiotics is greater than the discovery of novel antimicrobial agents. There is a need to study these antimicrobial patterns and, for this purpose, antibiograms should be developed at the levels of wards and hospitals and studied to guide us better on how to choose suitable empirical therapy for our patients. Methods and materials A total of 286 reports were studied, which contained the culture and sensitivity data of all the patients admitted under the care of Surgical Unit-1 in Lahore General Hospital between April 1, 2019, and October 31, 2019. All the samples for culture and sensitivity were sent to the in-house laboratory of the hospital where the reporting was done by the pathology department. They were inoculated and then intubated, and gram staining was performed. Antibiotic resistance and susceptibility were measured by the disk diffusion method according to the Clinical and Laboratory standards institute (CSLI) guidelines. Results The most common isolated organism was Escherichia coli​​​​​​​ (E. coli) in 65 (24%) patients, the next most common was Acinetobacter species in 62 (23%), followed by Pseudomonas species 52(19%), Klebsiella species 32 (13%), Staphylococcus aureus 30 (11%), Coagulase-negative Staphylococci 20 (7%), Enterobacter species (2%), and Citrobacter species (1%). The antimicrobial susceptibility of E. coli was highest for aminoglycosides and carbapenems like amikacin (78%), meropenem (71%), and imipenem (63%). Acinetobacter was most sensitive to colistin (100%), amikacin (31%), meropenem (21%), and cefoperazone + sulbactam (21%). Pseudomonas was also most sensitive to colistin (93%) and after that amikacin (52%), meropenem (52%), and imipenem (44%). Klebsiella was most sensitive to colistin (86%), imipenem (60%), and aminoglycosides (50%). Among gram-positive organisms, Staphylococcus aureus was sensitive to linezolid (100%) and vancomycin (100%). Conclusion The vast majority of isolated organisms in this study were gram-negative bacteria, and most were showing high antimicrobial resistance. The antibiograms should be developed and regularly updated at every ward and hospital. There is a need to bring more awareness about the proper use of antimicrobials among healthcare workers, and antimicrobial stewardship programs can help in this matter.